Caffeine consumption: are you aware? / Che Norhalila Che Mohamed ... [et al.]. - Che Mohamed, Che Norhalila; Mohd Basir, Nora; Zulkifli, Muhammad Luqman; Rahim, Muhammad Shauqi; Suhardi, Najmuddin Haqimi Nazli (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Caffeine is found naturally in certain plants, such as coffee, tea, soft drinks, and energy beverages. Its effects, including increased heart rate, faster breathing, and heightened alertness, typically start within five to thirty minutes and vary in duration from person to person. This study aims to explore the awareness of caffeine’s effects among students and the factors influencing this awareness. 397 randomly selected public university students in Negeri Sembilan participated in an email questionnaire. The analysis results indicate a notable association between daily caffeine consumption and gender. Additionally, 69.5% of the respondents are aware of the consequences of caffeine consumption. The findings from the logistic regression model demonstrate that knowledge and consumption significantly impact the level of awareness regarding the effects of caffeine consumption among students. It is essential to increase awareness among students and the community to ensure that all caffeine lovers can consume it more healthily.